Podcast-Enhanced Speaking Learning: A Study of Students’ Perceptions - Nurhidayat Nurhidayat (BAHTRA: Pendidikan Bahasa dan Sastra, 2026)
This study aims to explore students’ perceptions of podcast-enhanced speaking learning and identify its benefits and challenges in the EFL classroom at STKIP Taman Siswa Bima. The research employed a qualitative descriptive design supported by simple quantitative analysis. The participants were 25 second-semester students of the English Education Study Program. Data were collected through a Likert-scale questionnaire and semi-structured interviews. Quantitative data were analyzed using percentage calculations, while qualitative data were analyzed through thematic analysis, including data reduction, categorization, and interpretation. The findings revealed that students generally had positive perceptions toward the use of podcasts in speaking learning. Most students agreed that podcasts improved their pronunciation, fluency, confidence, and motivation in speaking English. Podcasts were also considered interesting and flexible learning media because students could access the materials anytime and practice independently. However, some students experienced difficulties in understanding fast speech and unfamiliar vocabulary. Despite these challenges, the study concludes that podcasts are effective tools for enhancing speaking skills by providing authentic language input and creating a more engaging learning environment. Therefore, lecturers are encouraged to integrate podcasts into speaking instruction with appropriate guidance and material selection to maximize learning outcomes